The Role of Brand on Educational Institution - Irpansyah, Muhamad Alvi; Chan, Arianis; Tresna, Pratami Wulan (Fakultas Ekonomi Universitas Samudra, 2023)
Brand is one of the strategies that can be carried out by educational institutions, including by building brand awareness, brand associations and perceived quality. The purpose of this study was to determine the effect of brand awareness, brand association and perceived quality on students' decisions in choosing SMK as a senior high school, both partially and simultaneously. The quantitative method with the type of causal descriptive research was implemented on 329 students of SMKN 1 Cianjur who were selected as samples. The results of the path analysis of the data show that brand awareness, brand associations and quality perceptions are proven to have a positive and significant influence, both partially and simultaneously on the purchasing decision process.